(untitled) - Max Quanchi (Cambridge, New York, 1991)
This is one of three books in the series "The Pacific in the 20th century". It covers key events and changes occuring in the recent history of the islands; traces the origins of the people of the Pacific through the archaeological evidence only recently being uncovered. This is history in the form of pottery, sea-level changes, canoe designs, art, oral myths and legends
Keywords: island of the pacific - history - 20th century